The Potential Role of Glucagon-Like Peptide-1 Receptor Agonists in Polycystic Ovary Syndrome: A Narrative Review - Turlej, Kamil; Kowalczuk, Dmytro; Kasianik, Viktoryia; Lazitskaya, Darya; Sobchynskyi, Mykola; Milasheuskaya, Valeryia; Myrnyi, Andrii; Kiełbaszewska, Iga; Surosz, Natallia; Miraniuk, Katsiaryna (Quality in Sport, 2025)
This narrative review explores the potential therapeutic role of Glucagon-Like Peptide-1 Receptor Agonists (GLP-1 RAs) in the management of Polycystic Ovary Syndrome (PCOS). PCOS is a multifaceted challenge affecting women, often associated with genetic susceptibility, obesity, and insulin resistance. The review seeks to provide a nuanced understanding of the interconnected health concerns of obesity and infertility in women with PCOS and critically analyse current data on the use of GLP-1 RAs as a potential treatment strategy in comparison to standard management of PCOS. It focuses on evaluating their impact on weight loss and associated metabolic parameters, drawing upon evidence from preclinical and clinical studies. While promising results have been observed, including potential benefits on endocrine and reproductive parameters, concerns regarding long-term safety, including serious adverse events, warrant further investigation. This review aims to summarise the current understanding of GLP-1 RAs in PCOS and highlight areas requiring additional research to fully establish their place in comprehensive PCOS management.